Bimatoprost-induced late-onset choroidal detachment after trabeculectomy: A case report and review of the literature. Issue 5 (February 2017) - Nakakura, Shunsuke; Noguchi, Asuka; Tabuchi, Hitoshi; Kiuchi, Yoshiaki
Abstract: Background: Choroidal detachment (CD) is often observed at an early period particularly after trabeculectomy and glaucoma drainage implant surgery. However, topical antiglaucoma eye drop-induced CD is a rare complication. Here, we report a case of topical bimatoprost-induced late-onset CD after trabeculectomy and review the literature. Case report: A 74-year-old man who suffered from primary open-angle glaucoma underwent his initial trabeculectomy with mitomycin-C in the right eye. Before the surgery, his intraocular pressure (IOP) was 20 to 22 mm Hg with bimatoprost 0.03%, dorzolamide 1%, and brimonidine 0.1% and his best corrected visual acuity (BCVA) was 0.9. The mean deviation in Humphrey Visual Field Analyzer (24–2 program) was −27.83 db. After successful trabeculectomy, IOPs were 11 to 16 mm Hg without any medication. Eight months after the surgery, we restarted bimatoprost to further reduce the IOP in the right eye, which was 15 mm Hg. At a hospital visit 2 months later, he complained of blurred vision that had persisted for the past 1 month; his IOP had decreased to 9 mm Hg. His BCVA was 0.04 and 3 quadrant CD was found. We discontinued bimatoprost and started him on betamethasone 0.1% 4 times per day. However, CD marginally changed after 1 week, with IOP at 7 mm Hg; thus, we performed scleral drainage for CD. After 3 weeks of drainage, CD completely disappeared. IOP increased to 16 mm Hg and BCVA was 0.7. However, 3 months after the drainage, IOP increased to 29 mm Hg, and needling revision was thus performed. After the surgery, IOP remained at 14 to 16 mm Hg without any glaucoma medication and CD recurrence. A review of the literature showed that various antiglaucoma medications induce CD, regardless of the preceding glaucoma surgery and that CD is usually resolved by withdrawing the medication and administering topical steroids. However, most previous studies have shown the recurrence of CD by rechallenging the same drug. Conclusion: In our case, topical bimatoprost induced late-onset CD after trabeculectomy. Early scleral drainage may be a good option to quickly resolve drug-induced CD and prevent its recurrence. Therefore, it must be kept in mind that various antiglaucoma medications induce CD.